2013
DOI: 10.1016/j.pain.2013.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in endogenous pain modulation in endurance athletes: An experimental study using quantitative sensory testing and the cold-pressor task

Abstract: There is evidence for long-term alterations in pain tolerance among athletes compared with normally active controls. However, scientific data on pain thresholds in this population are inconsistent, and the underlying mechanisms for the differences remain unclear. Therefore, we assessed differences and similarities in pain perception and conditioned pain modulation (CPM) at rest in endurance athletes and normally active controls. The standardised quantitative sensory testing protocol (QST) of the 'German-Resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
53
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 64 publications
6
53
2
2
Order By: Relevance
“…60 Triathletes' CPM was significantly enhanced compared to nonathletes', 18 and reduced responses to conditioning stimuli have been found in endurance athletes. 60 Interestingly, there was no early difference found between habituated and nonhabituated rats following exercise in this study. The nonhabituated rats' pain reduction following exercise was not different from the habituated rats' pain reduction 1 and 5 minutes following the exercise.…”
Section: Effect Of Habituationmentioning
confidence: 93%
See 2 more Smart Citations
“…60 Triathletes' CPM was significantly enhanced compared to nonathletes', 18 and reduced responses to conditioning stimuli have been found in endurance athletes. 60 Interestingly, there was no early difference found between habituated and nonhabituated rats following exercise in this study. The nonhabituated rats' pain reduction following exercise was not different from the habituated rats' pain reduction 1 and 5 minutes following the exercise.…”
Section: Effect Of Habituationmentioning
confidence: 93%
“…24,34 Studies on athletes have shown that their somatosensory processing differs in comparison with controls. Athletes demonstrated reduced sensitivity to mechanical pain, 60 reduced sensitivity to cold stimulation, 25 but increased sensitivity to vibration. 60 Triathletes' CPM was significantly enhanced compared to nonathletes', 18 and reduced responses to conditioning stimuli have been found in endurance athletes.…”
Section: Effect Of Habituationmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies on athletes have shown that their pain perception differs in comparison with the control group. Athletes had reduced sensitivity to cold and mechanical stimuli, 38,39 but increased sensitivity to vibration. 38 The increased response to vibration mediated by A-beta fibers (mechanical allodynia) is an interesting finding, as the vibration detection threshold was the only test that tends to gain more sensation (more sensitive perception).…”
mentioning
confidence: 97%
“…Athletes are a group particularly exposed to pain caused by injuries. A number of authors claim that athletes are more tolerant of pain and have higher pain thresholds compared to non-training population [2,3], which has been confirmed by numerous studies assessing the physiological, neurological, cultural and psychoanalytic causes of pain [4]. Researchers increasingly emphasize that athletes' conscious and unconscious attitudes, their motivations and anxiety levels (subjectively perceived risks) are elements which should be taken into consideration while investigating pain reactions.…”
mentioning
confidence: 99%